Clinical outcomes of open reduction and internal fixation combined with sartorius muscle iliac bone graft transplantation for displaced femoral neck fractures in middle-aged and young adults: a retrospective analysis of 24 cases - Hongfen Chen; Gen Wu; Shenglu Cao; Sushang Ma; Feng Huang; Pengfei Yang; Yihan Li; Hua Zhong (BMC Musculoskeletal Disorders)
Abstract Objective This study aimed to evaluate the clinical outcomes and complications of open reduction and internal fixation (ORIF) combined with sartorius muscle iliac bone graft transplantation (SIBFT) in the treatment of displaced femoral neck fractures in middle-aged and young adults. Methods A retrospective analysis was performed on 26 patients under the age of 60 with displaced femoral neck fractures (Pauwels III or Garden III-IV) treated at our institution between April 2019 to July 2022. All patients underwent open reduction and internal fixation (ORIF) through the Smith-Petersen (S-P) approach, augmented with a sartorius muscle iliac bone graft transplantation.The fractures were secured with either three cannulated screws or three cannulated screws combined with a medial support steel plate. Postoperative follow-ups were scheduled at 1, 2, 3, 6, and 12 months to record bone healing time, complications, and assess Harris Hip Scores. Results Two patients were lost to follow-up, resulting in 24 patients who completed the follow-up with an average duration of 25.7 months. Bone healing was observed in 95.8% (23/24) of the patients, with a mean healing time of 5.0 months. Avascular necrosis of the femoral head occurred in 8.3% (2/24) of the patients after fracture healing. Harris Hip Score at the last follow-up was 89.75 (range 73–98). Conclusion Our preliminary results suggest that ORIF combined with sartorius muscle iliac bone graft transplantation for the treatment of displaced femoral neck fractures in middle-aged and young adults achieved satisfactory clinical outcomes.